Bifrontal electroconvulsive therapy leads to improvement of cerebral glucose hypometabolism in frontotemporal dementia with comorbid psychotic depression – a case report - Sebastian Schröder; Lena Bönig; Phileas Johannes Proskynitopoulos; Eva Janke; Johannes Heck; Nima Mahmoudi; Adrian Groh; Georg Berding; Felix Wedegärtner; Stephanie Deest-Gaubatz; Hannah Benedictine Maier; Stefan Bleich; et al. (BMC Psychiatry, 2023)
Abstract Background Differentiating depression and dementia in elderly patients represents a major clinical challenge for psychiatrists. Pharmacological and non-pharmacological treatment options for both conditions are often used cautiously due to fear of adverse effects. If a clinically indicated therapy is not initiated due to fear of adverse effects, the quality of life of affected patients may significantly be reduced. Case presentation Here, we describe the case of a 65-year-old woman who presented to the department of psychiatry of a university hospital with depressed mood, pronounced anxiety, and nihilistic thoughts. While several pharmacological treatments remained without clinical response, further behavioral observation in conjunction with 18F-fluoro‐2‐deoxy‐D‐glucose positron emission tomography/computed tomography (18F-FDG PET/CT) revealed the diagnosis of frontotemporal dementia (FTD). To counter the pharmacological treatment resistance of psychotic depression, we decided to perform electroconvulsive therapy (ECT). Remarkably, ten sessions of ECT yielded an almost complete remission of depressive symptoms. In addition, the patient’s delusional ideas disappeared. A follow-up 18F-FDG PET/CT after the ECT series still showed a frontally and parieto-temporally accentuated hypometabolism, albeit with a clear regression compared to the previous image. The follow-up 18F-FDG PET/CT thus corroborated the diagnosis of FTD, while on the other hand it demonstrated the success of ECT. Conclusions In this case, ECT was a beneficial treatment option for depressive symptoms in FTD. Also, 18F-FDG PET/CT should be discussed as a valuable tool in differentiating depression and dementia and as an indicator of treatment response.